Inclusive Leadership and Proactive Personality in Fostering Innovative Work Behaviors: The Mediating Role of Creative Self-Efficacy among Employees in the Hotel and Tourism Sector - Davit Aditiya Pradana; Fatmah Bagis; Herni Justiana Astuti; Hermin Endratno (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
The rapid growth of the hospitality sector can contribute significantly to the expansion of the nation's economy, as the industry is highly competitive especially in developing cities Therefore, it is necessary to provide good services and processes. This study explores the influence of inclusive leadership and proactive personality on innovative work behaviors in the hospitality sector, with creative self-efficacy as a mediating variable. Data was collected from 162 hospitality and tourism employees using purposive sampling and questionnaires with a 5-point Likert scale, then analyzed using SEM-PLS. The results show that inclusive leadership, proactive personality, and creative self-efficacy significantly influence innovative work behaviors. The study is limited to the hospitality and tourism sectors. Future research should consider additional variables and a broader sample to gain a deeper understanding of the factors influencing innovative work behaviors.